Money, income and the Lucas critique: the case for Malaysia - Habibullah, Muzafar Shah; Azali, M.; Baharumshah, Ahmad Zubaidi (Universiti Utara Malaysia, 2001)
The objective of this study is to determine the usefulness of the monetary aggregates in Malaysia for policy action purposes. Money MI and M2 were tested for weak exogeneity, strong erogeneity and superexogeneity (which implies Lucas critique) within a seasonal error-correction model framework. Our weak exogeneity and superexogeneity tests suggest that money MI and M2 are not subject to the Lucas critique and thus imply that both monetary awegates are useful intermediate targets for monetary policy purposes. The importance of money as intermediate targets is further strengthened as our seasonal error-correction model indicates that money (MI and M2) and income exhibit stable long-run relationships.